Formation of raspberry (Rubus idaeus L.) new cultivars yield in the Ukrainian Right -Bank Lisosteppe - В. М. Остапенко; О. П. Лушпіган (Plant Varieties Studying and Protection)
The authors present the results of estimating seven raspberry cultivars - 'Novokutaivs'ka'(c), 'Phenomen' (c), 'Sanya', 'Perseya', 'Gusar', 'Kryepysh' and 'Strunka' - concerning their capability of forming yield depending on the cultivation year weather conditions. The cv 'Gusar' has been selected which had the highest yield of high-quality berries for two years of researches (2009-2010).